PERAN PEMERINTAH DAERAH PROVINSI DKI JAKARTA DALAM PEMENUHAN HAK PILIH BAGI PENYANDANG DISABILITAS PADA PEMILU PRESIDEN DI DKI JAKARTA TAHUN 2019 BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2016: The Role of The DKI Jakarta Provincial Government in Fulfillment Voting Rights for Persons with Disabilities in The Presidential Election in DKI Jakarta 2019 Based on Law Number 8 of the Year 2016 - Rajagukguk, Jessica Lamtiur; Wijiningsih, Ninuk (Faculty of Law, Universitas Trisakti, 2024)
The lack of participation from groups of people with disabilities in the 2019 presidential and vice presidential elections in DKI Jakarta is in the spotlight. The main issue in this jurnal is: Has Law No. 8 of 2016 concerning Disabilities provided a legal umbrella for fulfilling the right to vote for people with disabilities in the General Election for President and Vice President in the DKI Jakarta region in 2019, what are the efforts of the regional government in implementing the Law? Law No. 8 of 2016 concerning people with disabilities in order to fulfill the right to vote for people with disabilities in real actions and policies. This thesis writing uses a normative juridical research type, where secondary data is the main material and is analyzed qualitatively and conclusions are drawn deductively. Based on the results of this research and discussion, conclusions can be drawn, That Law No. 8 of 2016 concerning Persons with Disabilities has become a legal umbrella for groups of persons with disabilities, the Regional Government through the Special Capital Region of Jakarta Social Service is collaborating with the General Election Commission provide outreach regarding selection procedures through or phanages for people with disabilities